Production of biogas from poultry manure - Mohd Amirul Asyraf, Ahmad (2010)
The objective of this research is to determine the extent of anaerobic biodegradation of raw manure, co-digested manure with bran, and co-digested manure with grass (as the substitute for rice straw) at 10% TS w/v each, and to establish methane yields from these treatments. The anaerobic digestion of high solids raw manure and also co-digested manure were conducted in a 4 L batch anaerobic tank which operated under mesophilic conditions at ambient temperature. The co-digestion with grass (as substitute for rice straw) and bran were carried out to determine whether any of these two materials inhibited or promote the greater production of biogas. This co-digestion of high solids raw manure were conducted with a ratio of total solid of chicken manure to co digested material of 90:10 for both co-digestion. The result shows that, the anaerobic digestion of 10% TS w/v of chicken manure (without co-digestion) have 3 major phases that is the phase 1 or the lagging phase, that was believed to be the hydrolysis phase of the manure, which occurred in about 14 days, phase 2, the exponential phase that was believed to be the methanogenesis phase of the manure, which occurred about 49 days later, and phase 3, the end phase, that was believed to shows the last phase that is usually inhibited by ammonia and VFA concentration . The result shows that the co digestion with bran is more feasible which produce high yield of methane and lowest yield of hydrogen sulphide in biogas produce. The recommendation have been made to optimize the methane production by two stages of anaerobic digestion and also by inoculate to start the process